De « L’École du Mystère (xuanxue) » à Michel de Certeau : l’art de commenter les textes mystiques: From “Mystic Learning (xuanxue)” to Michel de Certeau: the Art of Commenting on Mystical Texts - Vermander, Benoît (Interdisciplinary journal for religion and transformation in contemporary society, 2025)
The term “Mystic Learning (xuanxue)” refers to a Chinese philosophical and mystical movement that was most active in the third century AD, although the investigative practices proper to the School are attested as late as the sixth century. It is associated with thinkers such as Wang Bi (226–249) and Guo Xiang (252–312). It corresponds to a creative revival of the founding texts of Taoism and of certain Confucian writings, while establishing a reflexive distance from the experience proposed by these original writings. This contribution brings such a revival closer to that attempted by Michel de Certeau in an entirely different context. It will look at the founding intuitions they may share. How do commentators give new life and relevance to “mystical” texts? How do they create new works by reading a corpus and reactivating its fruitfulness, which might have been thought to have dried up?